(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: Traditional Weaving using blackstrap loom called ‘puan-bu’ which is a symbol of discipline and prestige of a woman has been practiced among the Vaiphei Indigenous people of Manipur for several decades, and it has played an important role in the community, particularly among the women. However, no study of the corpus of recorded knowledge about Vaiphei Indigenous handicrafts on weaving has been conducted to date. This study aims to document the process involve in weaving, identify the equipment and raw materials use on the traditional loom among the Vaiphei’s. A semi-structured questionnaire was used to interview people between January 2021 and December 2022 to gather information about the Vaiphei tribe's traditional weaving in 3(three) different villages. From the study conducted, 33(thirty three) informants were interviewed and various weaving equipment and certain numbers of raw materials involved in weaving were identified. Traditional blackstrap loom weaving has been practiced by the Vaiphei’s for centuries, not only as a duty to provide for their family's basic needs but also as a discipline and honor. It is demonstrates to be of a highly regarded culture value in the society. But, According to surveys, the younger generations are uninformed of the skill and technique of weaving, as well as the traditional meanings of each traditional outfit. As such, the rich indigenous knowledge of the Vaiphei community faced a threat due to the process of modernization and other certain factors.